EFEKTIVITAS REVITALISASI PASAR REGIONAL DI KABUPATEN KLATEN - Cut Khusnul Khotimah; Murtanti Jani Rahayu; Rufia Andisetyana Putri (Jurnal Pengembangan Kota, 2017)
[Title: The Effectiveness of Regional Market Revitalisation in Kabupaten Klaten]. Regional market revitalization in Kabupaten Klaten was carried out as an effort to maximize regional economic activities. Hence, this research seeks to find out the levels of effectiveness of regional market revitalization in Kabupaten Klaten. The first stage of the research process was to find out the values of each component needed for revitalization in each regional market. The second stage was to discover the priority of each component of the revitalization by using AHP (Analytic Hierarchy Process) technique. The final step was to analyze the levels of effectiveness of the revitalization by multiplying results of the first stage by those of the second stage. The research found that the regional market revitalization in Klaten regency is categorized as ‘less effective’, because only one out of eight components needed for the revitalization was found to be maximally-applied—that is the component of range of services which is included in spatial aspects of regional markets. The other components, such as physical aspects comprising components of convenience and width, socio-economic aspects including components of sellers’ income and types of goods, as well as management aspects comprising components of management and security, are required to be improved to achieve effective regional market revitalization outputs.